2014
DOI: 10.1002/2013wr014212
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow to a pumping well in a sloping fault zone unconfined aquifer

Abstract: This study develops a mathematical model for simulating the hydraulic head distribution in response to pumping in a sloping fault zone aquifer under a water table boundary condition. A twodimensional equation with a sink term representing the pumping is used for describing the head distribution in the aquifer. In addition, a first-order free surface equation is adopted to represent the change in water table at the outcrop. The analytical solution of the model, derived by the Laplace and finite Fourier cosine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…In fact, the topic of flow in a sloping aquifer has long been investigated [e.g., Henderson and Wooding, 1964;Huang et al, 2014]. Steady state solutions of the nonlinear Boussinesq equation for homogeneous unconfined flow in sloping aquifers with recharge have been derived analytically by McEnroe [1993], Verhoest and Troch [2000], Chapuis [2002], and Lo aiciga [2005].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the topic of flow in a sloping aquifer has long been investigated [e.g., Henderson and Wooding, 1964;Huang et al, 2014]. Steady state solutions of the nonlinear Boussinesq equation for homogeneous unconfined flow in sloping aquifers with recharge have been derived analytically by McEnroe [1993], Verhoest and Troch [2000], Chapuis [2002], and Lo aiciga [2005].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the drawdown distribution versus time presented by our numerical solution and the solution of Huang et al (2014) with field data reported by Antonio and Pacheco (2002). …”
Section: Resultsmentioning
confidence: 69%
“…Generally, the upper boundary condition at the outcrop can be regarded as an infiltration curve which is treated as a boundary with recharge. Therefore, as shown in the study of Huang et al (2014), the outcrop boundary can be characterized by the free surface equation (similar to the water table), which can be expressed as: Kszgoodbreak=goodbreak−Syst,zgoodbreak=Wsinθgoodbreak−s0.25emand0.25emx0xxr,$$ K\frac{\partial s}{\partial z}=-{S}_y\frac{\partial s}{\partial t},z=W\sin \theta -s\ \mathrm{and}\ {x}_0\le x\le {x}_r, $$ where S y [−] represents the specific yield, W [L] represents the total length of the aquifer, x0=WcosθB/(sinθ)$$ {x}_0=W\cos \theta -B/\left(\sin \theta \right) $$, representing the location of the pumping well in the x ‐direction. xr=Wcosθ$$ {x}_r=W\cos \theta $$, representing the location of the outcrop in the x ‐direction.…”
Section: Conceptual Modelmentioning
confidence: 82%
See 2 more Smart Citations